Epidemiology and risk factors of uninvestigated dyspepsia, irritable bowel syndrome, and gastroesophageal reflux disease among students of Damascus University, Syria - Tareq Al Saadi; Amr Idris; Tarek Turk; Mahmoud Alkhatib (Springer, 2019)
Uninvestigated dyspepsia (UD), irritable bowel syndrome (IBS), and gastroesophageal reflux disease (GERD) are common disorders universally. Many studies have assessed their epidemiological characteristics around the world. However, such information is not known for Syria. We aim to estimate the epidemiologic characteristics and possible risk factors for UD, IBS, and GERD among students at Damascus University, Damascus, Syria. A cross-sectional study was conducted in July-September 2015 at a campus of Damascus University. A total of 320 students were randomly asked to complete the survey. We used ROME III criteria to define UD and IBS, and Montreal definition for GERD. In total, 302 valid participants were included in the analysis. Prevalence for UD, IBS, and GERD was 25%, 17%, and 16%, respectively. Symptom overlap was present in 46 students (15%), with UD + IBS in 28 (9.3%), UD + GERD in 26 (8.6%), and IBS + GERD in 14 (4.6%) students. Eleven (3.6%) students had symptoms of UD + IBS + GERD. Each of these overlaps occurred more frequently than expected by chance. Significant risk factors included cigarettes smoking, waterpipe consumption, and body mass index <18.5 kg/m2 for UD; female gender and three cups of coffee/d for IBS; and two cups of tea and one to five cigarettes/d for GERD. Risk factors for these disorders remain poorly characterized and need further investigations.